Dampak Game Online Terhadap Prestasi Belajar Siswa Di Smpn 17 Kota Bengkulu - Pratama, Muhammad Ramanda; Masterjon, Masterjon; Yul, Fadlul Amdhi (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This study aims to determine the impact of online games on the learning achievement of students in class IX A in the subject of Information and Communication Technology at SMPN 17 Bengkulu City. The research was conducted using qualitative methods. The source of data in this study were students of class IX A SMPN 17 Bengkulu City. Data collection techniques used in this research are observation, interviews and documentation. The stages of data analysis are preceded by data reduction, data presentation, then conclusion drawing. The results of this study indicate that there is a negative influence of the habit of playing online games at home on the learning achievement of students of SMPN 17 Bengkulu City in the 2013/2024 academic year. Students who play online games mostly come from middle class families with middle class economic ability. Students who play online games also have learning outcomes that are on average less than the KKM value set by the school, meaning that students who play online games are still unable to achieve better learning outcomes than those who do not play online games.